Aerosols: One‐Pot Preparation of Conducting Polymer‐Coated Silica Particles: Model Highly Absorbing Aerosols (Adv. Funct. Mater. 9/2014). (March 2014) - Lovett, Joseph R.; Fielding, Lee A.; Armes, Steven P.; Buxton, Ronald
<x xml:space="preserve">Abstract</x> Near‐monodisperse silica particles are surface‐modified by S. P. Armes and co‐workers using silanisation chemistry to aid the subsequent deposition of an ultrathin overlayer of an organic conducting polymer (polypyrrole) from aqueous solution. On page 1290, the resulting polypyrrole‐coated silica particles are readily dispersed in air and can be considered model highly‐absorbing aerosols, as well as synthetic mimics for silicate‐based micro‐meteorites. Their well‐defined core‐shell morphology is verified by selective digestion of the silica cores using HF to produce free‐standing polypyrrole shells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>